Anthelmintic Activity of Aqueous Extract of Pongamia pinnata Linn. - ANBU JEBA SUNILSON*, J.; JAYARAJ, P.; VARATHARAJAN, R.; ANANDARAJAGOPAL, K.; REJITHA, G.; SURAJ, R. (Asian Journal of Chemistry, 2009)
Anthelmintic activity of the various doses of aqueous extract ofPongamia pinnata Linn leaves was evaluated on earthworms (Pheretimaposthuma) and the results were compared with standard drug, albendazole(10 mg/mL). It was found that there was no final recovery in the case ofworms treated with aqueous extract of Pongamia pinnata. Aqueousextract of Pongamia pinnata Linn also exhibited dose dependant inhibitionof spontaneous motility (paralysis) and death of earthworms. Aqueousextract of Pongamia pinnata Linn showed highly significant (p < 0.001)anthelmintic activity at the concentration of 50 mg/mL. The resultsshowed that the aqueous extract of Pongamia pinnata Linn possesseswormicidal activity and be useful as an anthelmintic.